Genotype-Phenotype Correlation of 2q37 Deletions Including NPPC Gene Associated with Skeletal Malformations - Tassano, Elisa (Public Library of Science, 2013)
Coordinated bone growth is controlled by numerous mechanisms which are only partially understood because of the involvement of many hormones and local regulators. The C-type Natriuretic Peptide (CNP), encoded by NPPC gene located on chromosome 2q37.1, is a molecule that regulates endochondral ossification of the cartilaginous growth plate and influences longitudinal bone growth. Two independent studies have described three patients with a Marfan-like phenotype presenting a de novo balanced translocation involving the same chromosomal region 2q37.1 and overexpression of NPPC. We report on two partially overlapping interstitial 2q37 deletions identified by array CGH. The two patients showed opposite phenotypes characterized by short stature and skeletal overgrowth, respectively. The patient with short stature presented a 2q37 deletion causing the loss of one copy of the NPPC gene and the truncation of the DIS3L2 gene with normal CNP plasma concentration. The deletion identified in the patient with a Marfan-like phenotype interrupted the DIS3L2 gene without involving the NPPC gene. In addition, a strongly elevated CNP plasma concentration was found in this patient. A possible role of NPPC as causative of the two opposite phenotypes is discussed in this study.